Genome-wide association study of mitochondrial copy number. Issue 8 (23rd November 2021) - Gentiluomo, Manuel; Giaccherini, Matteo; Gào, Xīn; Guo, Feng; Stocker, Hannah; Schöttker, Ben; Brenner, Hermann; Canzian, Federico; Campa, Daniele
Abstract: Mitochondrial DNA copy number (mtDNAcn) variation has been associated with increased risk of several human diseases in epidemiological studies. The quantification of mtDNAcn performed with real-time PCR is currently considered the de facto standard among several techniques. However, the heterogeneity of the laboratory methods (DNA extraction, storage, processing) used could give rise to results that are difficult to compare and reproduce across different studies. Several lines of evidence suggest that mtDNAcn is influenced by nuclear and mitochondrial genetic variability, however this relation is largely unexplored. The aim of this work was to elucidate the genetic basis of mtDNAcn variation. We performed a genome-wide association study (GWAS) of mtDNAcn in 6836 subjects from the ESTHER prospective cohort, and included, as replication set, the summary statistics of a GWAS that used 295 150 participants from the UK Biobank. We observed two novel associations with mtDNAcn variation on chromosome 19 (rs117176661), and 12 (rs7136238) that reached statistical significance at the genome-wide level. A polygenic score that we called mitoscore including all known single nucleotide polymorphisms explained 1.11% of the variation of mtDNAcn (p = 5.93 × 10 −7 ). In conclusion, we performed a GWAS on mtDNAcn, adding to the evidence of the genetic background of this trait.